Adaptive Human Resource Management in Improving Employee Performance: A Literature Study - M Fahri Ramadhan; Havis Aravik; Ahmad Tohir (Jurnal Bisnis dan Manajemen (JURBISMAN), 2026)
The increasingly dynamic work environment due to technological developments, competency demands, and global uncertainty requires organizations to manage human resources more flexibly and responsively. This study aims to analyze how adaptive human resource (HRM) management plays a role in improving employee performance and building individual and organizational readiness to face change. The method used is a qualitative literature study through the review and synthesis of national and international scientific articles from 2020–2025 that discuss adaptive HRM practices and employee performance. The study results indicate that the implementation of flexible HRM policies, continuous competency development, a contextual performance management system, an organizational culture that supports learning, and the integrated use of digital technology can improve employee productivity, work quality, and adaptability. These findings also indicate that a supportive work environment and leadership that is open to change strengthen employee engagement and motivation, thus positively impacting individual and team performance. Therefore, it can be concluded that adaptive HRM is not merely a response to change but a crucial strategy for building resilient, competent, and competitive human resources, while supporting the long-term sustainability of organizational performance.